PENANAMAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN DI SMP SYABAB AL-FATIH SRI MULYA KECAMATAN PAMPANGAN KABUPATEN OGAN KOMERING ILIR - Indah Anggara; Fitri Oviyanti; Irja Putra Pratama (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
The Planting of Islamic Religious Education Values ​​in the Formation of Environmental Concerned Characters is a process to be achieved by educational institutions because by planting these noble values, one can know the extent to which students' awareness of caring for the environment by looking at the character development that grows in themselves gradually. This research is a type of descriptive qualitative research, with data collection techniques through observation, interviews and documentation. In this study using descriptive qualitative data analysis. The source of data in this study is primary data that is data obtained through observation and interviews with informants, while secondary data is obtained through documentation. Based on the results of the study showed that the inculcation of Islamic religious education values ​​in the formation of environmental care characters in Syabab Al-Fatih Sri Mulya Middle School, Pampangan District, Ogan Komering Ilir District was sufficient because the training, guidance, and learning efforts undertaken by all school members were able shape the character of caring for the environment through religious activities, SEMUTLI cleanliness program, and clean Friday conducted at school Likewise, factors that influence the formation of character consisting of internal and external factors. And also, can’t be separated from the role of teachers, students, the environment, and parents, who provide positive guidance and direction to foster the character of environmental care in students.